Eosin Y sensitized BiPO4 nanorods for bi-functionally enhanced visible-light-driven photocatalysis. Issue 6 (2nd April 2019) - Li, Boyuan; Zhang, Yuting; Duanmu, Fanpeng; Shen, Yongtao; Shen, Zhurui; Zhong, Shuhui
Abstract : Eosin Y sensitized BiPO4 nanorods enhanced the degradation efficiency of MB and 2, 4-DCP compared to pristine BiPO4 by 46.7 and 10.5 fold with a 100% mineralization rate. Abstract : In this work, we report a novel photocatalyst of Eosin Y dye sensitized BiPO4 nanorods via a low-temperature and impregnation adsorption method. It shows enhanced visible-light-driven photocatalytic activity for degrading methylene blue (MB) and 2, 4-DCP compared to that of pristine BiPO4 nanorods. The mass ratio of Eosin Y/BiPO4 is varied from 5 wt% to 30 wt% and the optimum value is 15 wt%, showing 46.7 and 10.5 fold greater apparent reaction rates than pristine BiPO4 . Moreover, all of the reduced MB was transformed into CO2 and H2 O during the photocatalysis, showing the good mineralization ability (almost 100%) of the composite. Furthermore, the photocatalytic mechanism of the composite is also investigated here by the zeta potential, scavenger experiments, Electron Paramagnetic Resonance (EPR), Photoluminescence Spectroscopy (PL), and a series of electrochemical analyses. The results show that (i) e − is the main reactive species and (ii) Eosin Y coated and adsorbed on BiPO4, thus widening the response range to the visible light region and accelerating the charge separation/transfer, resulting in bi-functionally promoted activity.